ABE'S FOREIGN POLICY - Hideaki Shirakata (Yogyakarta State University, 2018)
The essay seeks to examine the Japanese Prime Minister, Shinzo Abe’s security diplomacy in responsive to changes in the security environment surrounding Japan. The data referred in the essay is from the secondary sources, mainly academic journals and books. The finding showed that due to external threat, a bold move was made to pass the security bills despite a major protest. Moreover, under his theme of diplomacy named “proactive peace diplomacy”, it appears that he aims to form a Japan-led-security alliance in the region. In spite of this, Japan is embedded in the Asia context on the axis of the Japan-US security alliance. As long as the constitutional constraints, especially the article 9 clause are concerned, the pursuit of independent foreign policy would be limited.